2022
DOI: 10.3389/fcimb.2022.957439
|View full text |Cite
|
Sign up to set email alerts
|

A thousand metagenome-assembled genomes of Akkermansia reveal phylogroups and geographical and functional variations in the human gut

Abstract: Akkermansia muciniphila has long been considered to be the only Akkermansia species in the human gut and has been extensively studied. The present study revealed the genomic architecture of Akkermansia in the human gut by analyzing 1,126 near-complete metagenome-assembled genomes, 84 publicly available genomes, and 1 newly sequenced Akkermansia glycaniphila strain from the human gut. We found that 1) the genomes of Akkermansia were clustered into four phylogroups with distinct interspecies similarity and diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…The clade A comprised A. muciniphila and other related species (GTDB names sp900545155, sp905200945, muciniphila_A, muciniphila_B, muciniphila_E, muciniphila_C, sp001580195, sp004167605, and Cluster25, without no specific species level classification in GTDB). Compared with previous studies ( Karcher et al, 2021 ; Lv et al, 2022 ), the GTDB A. muciniphila genomic species corresponds to the Amuc I phylogroup, whereas Akkermansia muciniphila_B corresponds to Amuc II , Akkermansia muciniphila_C to Amuc III , and Akkermansia sp001580195 to Amuc IV . On the other hand, Clade B includes A. glycaniphila, Ca .…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…The clade A comprised A. muciniphila and other related species (GTDB names sp900545155, sp905200945, muciniphila_A, muciniphila_B, muciniphila_E, muciniphila_C, sp001580195, sp004167605, and Cluster25, without no specific species level classification in GTDB). Compared with previous studies ( Karcher et al, 2021 ; Lv et al, 2022 ), the GTDB A. muciniphila genomic species corresponds to the Amuc I phylogroup, whereas Akkermansia muciniphila_B corresponds to Amuc II , Akkermansia muciniphila_C to Amuc III , and Akkermansia sp001580195 to Amuc IV . On the other hand, Clade B includes A. glycaniphila, Ca .…”
Section: Resultscontrasting
confidence: 64%
“…Recently, comparative genomics and A. muciniphila pangenome studies have been performed multiple times ( van Passel et al, 2011 ; Guo et al, 2017 ; Xing et al, 2019 ; Lv et al, 2020 ; Geerlings et al, 2021 ; Karcher et al, 2021 ; Kim et al, 2022 ; Li et al, 2022 ; Lv et al, 2022 ; Ouwerkerk et al, 2022 ). However, the use of an Orthofinder-based strategy is not common.…”
Section: Resultsmentioning
confidence: 99%
“…Another effect of ICR is the decrease of Verrucomicrobia, which in our study appeared as early as 2 days after removal of the cecum and which in rats remained decreased even 28 days after 75% ICR ( 10 ). To date, Akkermansia muciniphila and, more recently, also Akkermansia glycaniphila have been isolated from the human intestine, the latter being found preferentially in nonmammals ( 34 ). A. muciniphila is widely distributed in the intestines of human and mice where it colonizes the outer mucosal layer, being most abundant in the cecum ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Amuc4 was more commonly found in non-Westernized human populations compared to non-Amuc4 species. Analysis of metagenome-assembled genomes of Akkermansia revealed that Amuc III mainly distributed in the Chinese population and Amuc IV was more commonly present in Western populations, whereas Amuc I and II distributed extensively globally ( Lv et al, 2022 ). The representative genomes of Amuc I, II, III, and IV showed diversified genomic characteristics involved in multiple metabolism and transport pathways, which suggests different evolution history and functional habits.…”
Section: Genome Diversity and Properties Of Akkermansia Muc...mentioning
confidence: 99%